Business R&D expenditure and capital in Europe - Christian Helmers; Christian Schulte; Hubert Strauss (EIB Papers, 2009)
This study presents new estimates of business R&D capital stocks for 22 countries at the aggregate and industry levels. At 9 percent of GDP, the EU business R&D capital stock falls short of its US and Japanese counterparts. Within the EU, R&D capital stocks are much lower in the southern and the new member states, reflecting large and persistent disparities in R&D expenditure. There was hardly any convergence over the past decade. The R&D capital stock is concentrated on three technologyintensive manufacturing industries and is positively correlated with growth in total factor productivity across countries and industries. Finally, the ratios between the stocks of R&D capital and tangible capital suggest marked differences in how R&D and tangible capital are combined in production.
Keywords: 330; Industrielle Forschung; Gesamtwirtschaftliches Anlagevermögen; Forschungskosten; Produktivität; Betriebliches Anlagevermögen; Branche; EU-Staaten; Japan; USA